Computing in Civil and Building Engineering (2014) 2014
DOI: 10.1061/9780784413616.244
|View full text |Cite
|
Sign up to set email alerts
|

BIM in Sustainable Design: Strategies for Retrofitting/Renovation

Abstract: Improving the performance of existing buildings has provided a broad market for the green renovation of US building stock which is estimated at 76 billion square feet. Building Information Modeling (BIM) has had tremendous impact on the building industry by increasing productivity and document accuracy alone. The integrative nature of BIM technology renders it an ideal tool for implementing sustainable strategies into the renovation and/or retrofit of existing structures.By exploring the nature of the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…By applying BIM technology, users can make precise decisions and promote the process of construction" [3]. Similarly, as an innovative digital tool, BIM is widely applied in the life cycle of a project for visualization, scheduling, communication, and teamwork among project construction, as well as to promote the process of forming, accumulating, controlling, transforming, and delivering construction data in an effective manner [4]. BIM can generate a computer-based three-dimensional model to visualize the whole life-cycle process of construction involving the phase of planning, design, construction, and operation [5].…”
Section: Introductionmentioning
confidence: 99%
“…By applying BIM technology, users can make precise decisions and promote the process of construction" [3]. Similarly, as an innovative digital tool, BIM is widely applied in the life cycle of a project for visualization, scheduling, communication, and teamwork among project construction, as well as to promote the process of forming, accumulating, controlling, transforming, and delivering construction data in an effective manner [4]. BIM can generate a computer-based three-dimensional model to visualize the whole life-cycle process of construction involving the phase of planning, design, construction, and operation [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, without detailed prediction and planning for the types and volumes of recycled building materials, it can be time-consuming and expensive for contractors and recyclers to conduct a material recycling process [32]. If a building is • Wu and Issa [110] • Zhai and McNeill [117] • Hammond et al [50] • Frank et al [43] • • Jalaei and Jrade [55] • Wu et al [111] • Zuo and Zhao [118] • Wong and Kuan [104] • Inyim et al [54] • Volk et al [101] • • • Lin and Gerber [71] • Katranuschkov et al [58] • Kandil et al [119] • Gandhi and Jupp [44] • Russell-Smith and Lepech [90] • • • • • Wong et al [106] • Eadie et al [40] • Costa et al [36] • Cooley and Cholakis [120] • Costin et al [37] • Clevenger and Khan [34] • Cheng and Ma [32] • Chi et al [33] • • • Wong and Lau [105] • Yeheyis et al [113] • • Wong and Fan [107] • Buyle et al [27] • König et al [61] • Jrade and Jalaei [57] • Motawa and Almarshad [79] • Motawa and Carter [80] • • • • • • Liao et al [70] • Wu and Issa [108] • Rajendran et al [89] • Rajendran and Gomez [88] • • Cheng and Ma [31] • Jiang et al [56] • Bynum et al [28] • • Azhar et al [15] • Chang et al …”
Section: Building Demolitionmentioning
confidence: 98%
“…Through the use of three-dimensional virtual modelling, the sun path of the studied region was simulated to evaluate the amount of rooftop area that would not be affected by the shadows cast from the adjacent buildings. Hammond et al [50] established the 'Sustainable Framework' and 'Best Practices' for green retrofitting. Their research findings suggested that BIM integration helps to implement sustainable design principles into the renovation or retrofitting of existing buildings.…”
Section: Building Repair and Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…It differs from our work in the fact that it deals with prefabricated elements for the improvements of building characteristics. Hammond et al (2014) studied how professionals use BIM in retrofitting and renovation and how it affects their practice. They investigated a renovation process that had the goal of utilizing BIM "in as many areas as possible" with a view to comply with LEED rating system.…”
Section: Renovation Processesmentioning
confidence: 99%